NCOG-46. WHITE MATTER TRACT INVOLVEMENT BY INTRA-AXIAL BRAIN TUMORS; DIAGNOSTIC & THERAPEUTIC IMPLICATIONS. (12th November 2021) - Bakhshi, Saqib Kamran; Quddusi, Ayesha; Mahmood, Danish; Waqas, Muhammad; Shamim, Muhammad Shahzad; Mubarak, Fatima; Enam, Syed Ather
Abstract: Diffusion tensor imaging (DTI) is a relatively recent modality which aids in visualization of WMT and their relation to intracranial lesions. Despite almost two decades since the beginning of its use in tumor resection, there is still dearth of data on its diagnostic and prognostic value from low- and middle-income countries. We aimed to assess the pattern of involvement of white matter tracts (WMT) by intra-axial brain tumors on DTI. Secondary objectives were to evaluate implications of involvement of WMT on surgical resection, and post-operative functional outcome. This was a retrospective study of 77 consecutive patients, who underwent DTI guided surgery for brain tumors. The involvement of WMT by tumors on DTI was assessed by a radiologist (who was blind to the pathology) using the Witwer classification. The pathology was reported by histopathologists using WHO brain tumor classification. Karnofsky Performance Scale (KPS) was used for assessing patients' neurological status at admission, and at follow-up. Forty-five (58.4%) out of 77 tumors reviewed, caused infiltration of WMT, whereas only 22 (28.6%) tumors caused displacement of WMT ( p = 0.040). Among 32 cases of astrocytoma, involvement of WMTs was influenced by the grade of tumor ( p = 0.012), as high-grade tumors caused infiltration (19; 59.4%), unlike low grade tumors which commonly caused displacement (2; 50%). Oligodendroglioma caused infiltration/disruption of WMTs in most cases, irrespective of the grade (19 out of 25 cases; 76%). At last follow-up, 27 (35.1%) patients showed improvement in KPS and 14 (18.2%) reported deterioration, while there was no change observed in 36 (46.8%) patients. Infiltration of WMTs was associated with poor functional outcome. We conclude that intra-axial brain tumors mostly cause infiltration of WMTs, particularly high-grade astrocytoma, and oligodendroglioma of any grade. Infiltration of WMTs is associated with poor functional outcome at follow-up.